The Relationship between Short Story Reading Intensity and Elementary School Students' Reading Skills - Rizki Nurliana; Retno Wahyuningsih (JENIUS (Journal of Education Policy and Elementary Education Issues), 2023)
A person's low interest in reading can result in a lack of information which causes knowledge to be less developed. This research aims to determine the intensity of short story reading and students' reading skills as well as the relationship between these two variables in class II students at 017 Public Elementary School Tanjungpinang Timur, Kepulauan Riau. Researchers use quantitative correlational research. The population used was 76 students in classes III/b and III/c with a sample of 64 students. The sampling technique uses a purposive sampling technique. The instruments used in data collection were performance and questionnaires. The data analysis technique used in this research is hypothesis testing using the Spearman rank correlation formula. The research results showed that the intensity of reading short stories was in the medium category, 43 students or around 64% of 64 students; the students' reading skills were in the medium category; and 38 students or around 59% of 64 students. Based on hypothesis test calculations using SPSS 25 software, a sig value was obtained. 0.000 < 0.05, then there is a correlation between variables so that H1 is accepted while H0 is rejected, thus indicating that there is a positive relationship between the intensity of reading short stories and students' reading skills. Schools are expected to empower students' reading skills through the habit of increasing reading intensity